(3GdCMLGQs - (3CMeO Hf jhSa Hf CMeO Hf CHj HcQ Hf MeOhf GdbjSj GdJjaGTj , TQa GdOjf,J (B651 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdEfSGf Ydi LejY GdMjhGf CeG HYO aEfi CdaJ cJGHkG ai NhGU GdCMLGQ hQJHJg Ydi ebOeg hNeSI hYTQhf HGHkG s
(3BNQgG (B:s
(3hCf LYd eY GdaVI hGdPgH GdSHcI deG ajg ef GdQUGU hGddg CYde s
(3fSNI KGefIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI JjehQ (B91) s
Keywords: (3GdcjejGA h GdWHjYjGJs